Inactivation of the Pyrimidine Biosynthesis pyrD Gene Negatively Affects Biofilm Formation and Virulence Determinants in the Crohn’s Disease-Associated Adherent Invasive Escherichia coli LF82 Strain - Elio Rossi; Gabriella Leccese; Valerio Baldelli; Alessia Bibi; Emanuele Scalone; Carlo Camilloni; Moira Paroni; Paolo Landini (Microorganisms, 2022)
In Crohn’s disease (CD) patients, the adherent-invasive Escherichia coli (AIEC) pathovar contributes to the chronic inflammation typical of the disease via its ability to invade gut epithelial cells and to survive in macrophages. We show that, in the AIEC strain LF82, inactivation of the pyrD gene, encoding dihydroorotate dehydrogenase (DHOD), an enzyme of the de novo pyrimidine biosynthetic pathway, completely abolished its ability of to grow in a macrophage environment-mimicking culture medium. In addition, pyrD inactivation reduced flagellar motility and strongly affected biofilm formation by downregulating transcription of both type 1 fimbriae and curli subunit genes. Thus, the pyrD gene appears to be essential for several cellular processes involved in AIEC virulence. Interestingly, vidofludimus (VF), a DHOD inhibitor, has been proposed as an effective drug in CD treatment. Despite displaying a potentially similar binding mode for both human and E. coli DHOD in computational molecular docking experiments, VF showed no activity on either growth or virulence-related processes in LF82. Altogether, our results suggest that the crucial role played by the pyrD gene in AIEC virulence, and the presence of structural differences between E. coli and human DHOD allowing for the design of specific inhibitors, make E. coli DHOD a promising target for therapeutical strategies aiming at counteracting chronic inflammation in CD by acting selectively on its bacterial triggers.